Pretreatment Axillary Nodal Volume as a Prognostic Factor for Breast Cancer - Yuri Jeong; Jung Hoon Kim; Su Ssan Kim; Jinhong Jung; Ji Hyeon Joo; Hwa Jung Kim; Hak Hee Kim; Joo Hee Cha; Hee Jung Shin; Seung Do Ahn (The Breast Journal)
Conclusions: In breast cancer patients treated with neoadjuvant systemic therapy, larger pretreatment axillary nodal volume was associated with poor survival outcomes.